Pengaruh Job Crafting terhadap Work Engagement pada Guru Sekolah Dasar Negeri di Bandung - Fernanda Dwi Fadhilah; Djamhoer, Temi Damayanti (UNISBA Press, 2024)
Abstract. Work engagement in an organization is an important thing to pay attention to because it is very important for the overall work function of employees and the sustainability of the organization. One of the efforts to increase work engagement is by doing job crafting or modification in work. This study aims to determine how much influence job crafting has on work engagement in elementary school teachers. The research method used is the causality method through multiple regression analysis with 373 public elementary school teachers in Bandung as subjects, including 10 elementary schools in Bandung City and 4 elementary schools in Bandung Regency. The measuring instruments used in this study are Job Crafting Scale developed by Tims [10], and adapted by Astuti (2023) and Utrecht Work Engagement Scale developed by Schaufeli & Bakker [12]. The results showed that public elementary school teachers in Bandung had a high level of job crafting, which amounted to 96.8%. In addition, the teachers also have a high level of work engagement, which is 99.2%. The effect of job crafting on work engagement found is 52% with the increasing structural job resources dimension as the dimension that has the highest value. Increasing structural job resources is done through efforts to utilize opportunities to develop and optimize personal abilities. Abstrak. Keterikatan kerja atau work engagement pada suatu organisasi merupakan hal yang penting untuk diperhatikan karena sangat penting untuk keseluruhan fungsi kerja karyawan dan keberlanjutan organisasi. Salah satu upaya untuk meningkatkan work engagement adalah dengan melakukan job crafting atau modifikasi dalam pekerjaan. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh job crafting terhadap work engagement pada guru sekolah dasar. Metode penelitian yang digunakan adalah metode kausalitas melalui analisis regresi berganda dengan 373 guru Sekolah Dasar Negeri di Bandung sebagai subjek, mencakup 10 SDN di Kota Bandung dan 4 SDN di Kabupaten Bandung. Alat ukur yang digunakan dalam penelitian ini adalah Job Crafting Scale yang dikembangkan Tims [10], dan diadaptasi oleh Astuti (2023) dan Utrecht Work Engagement Scale yang dikembangkan oleh Schaufeli & Bakker [12]. Hasil penelitian menunjukkan bahwa Guru Sekolah Dasar Negeri di Bandung memiliki tingkat job crafting yang tinggi, yaitu sebesar 96.8%. Disamping itu, para guru juga memiliki tingkat work engagement yang tinggi, yaitu sebesar 99.2%. Pengaruh job crafting terhadap work engagement yang ditemukan adalah 52% dengan dimensi increasing structural job resources sebagai dimensi yang memiliki nilai paling tinggi. Increasing structural job resources dilakukan melalui upaya pemanfaatan kesempatan untuk mengembangkan dan mengoptimalkan kemampuan diri.